THE EFFECT OF AQUEOUS GARLIC EXTRACT AND CHROMIUM CHLORIDE COMPLEMENT ON TISSUE ANTI OXIDANT SYSTEM OF MALE RATS - J. G. Ghalehkandi; Y. Ebrahimnezhad; N. M. Sis (Journal of Animal and Plant Sciences, 2013)
An experiment was planned to study the protective role of aqueous garlic extract (AGE) on tissue anti-oxidant system malondialdehyede (MDA) superoxide dismutase (SOD), glutathione peroxidase (GPX) and catalase (CAT) concentrations in Chromium Chloride (CrCL3) challenged male Wistar rats (n= 162). The animals in nine treatments including three levels of AGE (0, 60 and 120 mg/rat/day) and CrCL3 (0, 4 and 8 mg/kg diet) were fed (over a period of 4 weeks). At the end of feeding trail, six rats per treatment were selected randomly and their blood was collected for analyses. The results showed that different levels of AGE and CrCL3 supplement, significantly increased the content of SOD, GPX and CAT (P<0.05) and decreased the concentration of MDA (P<0.05). Furthermore, the study of combinative effects of AGE and CrCL3 showed that anti oxidant enzymes levels (SOD, GPX and CAT) and MDA were higher and lower when compared to control groups, respectively (P<0.05).This study suggested that addition of AGE and CrCL3 had positive effects on antioxidant defense mechanisms and reduce the susceptibility of blood to free radical oxidative damage.
Keywords: Garlic; Chromium Chloride; malondialdehyde; tissue anti-oxidants